Photoinduced Pyramidal Inversion Behavior of Phosphanes Involved with Aggregation‐Induced Emission Behavior. Issue 36 (5th June 2020) - Machida, Takashi; Iwasa, Takeshi; Taketsugu, Tetsuya; Sada, Kazuki; Kokado, Kenta
Abstract: Aggregation‐induced emission (AIE) is a fascinating phenomenon because of the applications of luminescent materials in the aggregated state, which exploit the large structural changes of the molecules in the excited state. Recently, it was reported that triphenylphosphane derivatives show AIE behavior in which they undergo potentially large structural changes in the excited state. Inspired by this report, photoinduced pyramidal inversion behavior of phosphanes was investigated. In photochemical experiments, the prepared P‐stereogenic phosphanes exhibited photoracemization in dilute solution, and a negative correlation was observed between the photoracemization and the AIE phenomenon. Theoretical computations revealed that the inversion barrier in the excited state was much smaller than that in the ground state. This is the first report on the photoinduced pyramidal inversion behavior of phosphanes, which will provide new and unexplored applications. Abstract : Inverting the pyramid : Inspired by the aggregation‐induced emission (AIE) behavior of phosphanes, for the first time the photoinduced pyramidal inversion behavior of phosphanes in dilute solution was investigated. As expected, phosphanes are inverted under photoirradiation; the inversion mechanism could be explained by quantum chemical calculations (see figure).